2022
DOI: 10.1002/advs.202202781
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Haze‐Free Antireflective Hierarchical Surface with Self‐Cleaning Capability

Abstract: The lotus effect indicates that a superhydrophobic, self-cleaning surface can be obtained by roughening the topography of a hydrophobic surface. However, attaining high transmittance and clarity through a roughened surface remains challenging because of its strong scattering characteristics. Here, a haze-free, antireflective superhydrophobic surface that consists of hierarchically designed nanoparticles is demonstrated. Close-packed, deep-subwavelength-scale colloidal silica nanoparticles and their upper, chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…A patterned sample was annealed to promote adhesion for several hours in an oven at 50 °C (Figure S19, Supporting Information). [51] To achieve superhydrophobicity, the patterned sample was treated with 1H,1H,2H,2H-perfluorodecyltrimethoxysilane (HTMS, Sigma-Aldrich) of 5 wt% solution in hexane (Duksan Pure Chemicals, Korea) using a spraying process (similar to the nanostructuring process), followed by additional annealing at 50 °C in an oven. Finally, the superhydrophobic/hydrophilic patterned sample was realized after careful removal of the Kapton tape.…”
Section: Methodsmentioning
confidence: 99%
“…A patterned sample was annealed to promote adhesion for several hours in an oven at 50 °C (Figure S19, Supporting Information). [51] To achieve superhydrophobicity, the patterned sample was treated with 1H,1H,2H,2H-perfluorodecyltrimethoxysilane (HTMS, Sigma-Aldrich) of 5 wt% solution in hexane (Duksan Pure Chemicals, Korea) using a spraying process (similar to the nanostructuring process), followed by additional annealing at 50 °C in an oven. Finally, the superhydrophobic/hydrophilic patterned sample was realized after careful removal of the Kapton tape.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the material undergoes almost no degradation even after a long-term compressive cycle between 0 and 90% strains. In 2022, Oh et al [222] designed a superhydrophobic surface which combines the antireflective and self-cleaning properties via hierarchically engineered nanoparticles. The self-cleaning property and broadband antireflection are separately carried out by chain-like fumed silica nanoparticles and their lower closely packed, deep subwavelength scale colloidal silica nanoparticles.…”
Section: The Strategy Acting Between Substrates and Coatingsmentioning
confidence: 99%
“…[31,32] However, it was reported that the superhydrophobic materials prepared by most methods have poor abrasion resistance when damaged by external pollution or external force, which greatly limited the development and application of superhydrophobic materials. [33][34][35][36][37] In order to solve these problems, plenty of scholars have proposed different methods to improve the abrasion resistance of superhydrophobic surfaces, [38][39][40] such as reasonably designing the micro-nano structures and selecting materials, [41][42][43] optimizing the preparation process, [44,45] and the proportion of materials. [46][47][48][49][50] Although researches improving superhydrophobic abrasion resistance have made considerable progress, there are still many shortcomings, such as the lack of widespread applications.…”
Section: Introductionmentioning
confidence: 99%